Critical evaluation of parameters affecting Cu nanoparticles formation and their activity in dimethyl adipate hydrogenolysis - Aubrecht, Jaroslav; Pospelova, Violetta; Kikhtyanin, Oleg; Veselý, Martin; Kubička, David (Catalysis today, 2022)
Supported copper catalysts are promising alternative to replace CuCr catalysts in ester hydrogenolysis and decrease the environmental footprint of the process. However, the effect of the support properties on the Cu nanoparticles formation and, consequently, on the final hydrogenolysis performance has not been investigated in detail. Therefore, we have selected 10 supports with different textural-structural properties and impregnated them by incipient wetness impregnation to achieve 8 wt% Cu loading. Although the silica-based supports provided much larger surface area to deposit Cu compared to ZnO, MgO, or TiO2, the final Cu dispersion was similar for these catalysts due to the insufficient electrostatic attraction. A significant improvement was observed when using ZrO2 as a support, while the best Cu dispersion was achieved using alumina-based supports. The reduced catalysts were tested in dimethyl adipate (DMA) hydrogenolysis to obtain hexane-1,6-diol (HDOL). Due to the good Cu dispersion ensured by ZrO2 and alumina supports, they outperformed the rest of the catalysts reaching the highest DMA conversion of 36 and 22–25%, respectively. Moreover, Cu-ZrO2 reached the highest hydrogenolysis activity (TOFH) due to a good copper-zirconia interaction. The maximum HDOL selectivity of about 8% was obtained over alumina-based catalysts. The increasing number of acid-base sites was found to be responsible for decreasing HDOL selectivity. Over these sites, a large amount of transesterification by-products (<80%) and other side products were formed. Although the larger support surface area may ensure a better Cu dispersion, the acid-base sites or electrostatic attraction during impregnation play a key role by affecting the Cu nanoparticle formation and, consequently, the final catalyst performance. [Display omitted] •Cu-ZrO2 is the most active catalyst in dimethyl adipate hydrogenolysis.•Al2O3 ensures the best Cu dispersion.•IWI is not efficient method to deposit Cu on SiO2, ZnO, MgO and TiO2 supports.•Acid-base properties and point of zero charge affect the Cu dispersion.